(Re)Introducing communication competence to the health professions - Brian H. Spitzberg (SAGE Publishing, 2013)
Despite the central role that communication skills play in contemporary accounts of effective health care delivery in general, and the communication of medical error specifically, there is no common or consensual core in the health professions regarding the nature of such skills. This lack of consensus reflects, in part, the tendency for disciplines to reinvent concepts and measures without first situating such development in disciplines with more cognate specialization in such concepts. In this essay, an integrative model of communication competence is introduced, along with its theoretical background and rationale. Communication competence is defined as an impression of appropriateness and effectiveness, which is functionally related to individual motivation, knowledge, skills, and contextual facilitators and constraints. Within this conceptualization, error disclosure contexts are utilized to illustrate the heuristic value of the theory, and implications for assessment are suggested.